Mechanistic Insights into Phosphorus Efficiency and Shoot P Concentration in Chinese Cabbage - Ruifang Zhang; Saisai Hou; Chi Zhang; Hong Wang; Xinxin Wang (Agronomy, 2025)
Phosphorus (P) is vital for the growth of crops, and its absorption efficiency is closely linked to the traits of the plants. Further research is needed to understand how vegetable crops adjust to changes in P availability and how their root morphology and physiology are affected by high P levels in the shoots. In this study, eight Chinese cabbage (Brassica rapa pekinensis) genotypes were grown in a culture room under 0, 25, 50, 100, 150, 300, 600, 900, and 1200 mg kg−1 concentrations of P to evaluate root responses in order to define various adaptive strategies in relation to P acquisition. We selected high-PE and low-PE Chinese cabbage in order to identify how different P efficiency groups responded to P supply and shoot P concentration. P supply level and shoot P concentration significantly affected growth. With the increase in the P supply level, the growth variable characteristics of Chinese cabbage first increased and then decreased or increased first and then stabilized. But it was found that P300 was the most suitable level for Chinese cabbage growth. At the same P supply level, high-PE cabbages had higher shoot dry weight and P absorption capacity, stronger root traits, and higher plasticity as compared to low-PE cabbages. The optimal shoot P concentration is 2.1 mg g−1 and 1.7 mg g−1 for low- and high-PE cabbages, respectively. The root morphological traits performed greatly when the shoot P concentration was at the optimal concentration. The low-PE cabbages had greater shoot growth traits, and high-PE cabbages had higher root dry weight and P absorption. This study offers valuable insights to improve P management by analyzing the relationships between soil P dynamics and root processes in the cultivation of Chinese cabbage.